High sensitivity measurements of gas transport through films for food packaging and the O2 adsorption issue. (April 2023) - Schott, Marine; Setina, Janez; Vassallo, Espedito; Pedroni, Matteo; Campardelli, Roberta; Perego, Patrizia; Repetto, Luca; Firpo, Giuseppe
Abstract: New biodegradable polymers employed for food packaging require an accurate characterization of their O 2 ultra-barrier permeation rates. Methods and procedures of gas transport measurements must guarantee high sensitivity and immunity to artefacts. Within this context, this paper reports two outcomes. The first one is to demonstrate the suitability of a specific high vacuum apparatus for challenging measurements of gas permeability on new polymers for food packaging. We show that our newly developed set-up is able to achieve a minimum detectable gas throughput 2 × 10 - 9 m b a r l / s, which is equivalent to permeability coefficient of 7 × 10 − 11 c m 2 / s in case of 20 μm-thick polymer film with an area of 7 × 10 − 2 c m 2 under a 10 5 P a pressure differential. The second aim is to investigate the origin of its detection limits and possible measurement artefacts obtained with this instrument. In particular, we focus on the O 2 adsorption effect on the inner surfaces of the set-up. Highlights: Accurate gas transport measurements through films for food packaging. Manometric set-up in high vacuum for O2 and CO2 gas permeability measurements. Detection limits of mass spectrometer techniques: O2 adsorption on surfaces.